The benefits of tourism from community perspective of Chembe Village, Malawi - Chimangeni, Christine Pokaniso (My University, 2015)
The Malawi National Tourism Policy’s mission is to ensure that tourism brings meaningful economic benefits to host communities and thereby reduce poverty. However, it remains unclear whether Chembe village in Mangochi is benefiting as the district still registers low literacy levels and a high rate of malnourished children. This study aimed at understanding the socio-economic benefits of tourism to this village and particularly how community participation and a low level of education affect the attainment of benefits. A qualitative study, following a case study design, was conducted and data was collected through semi-structured interviews and focus group discussions. The study revealed that Chembe Village is benefiting from tourism through employment, Small and Medium Enterprises, exposure and infrastructural development despite the residents’ low level of education and minimal community participation due to lack of proper co-ordination between the leaders and residents. Nevertheless, income generated through employment and the Small and Medium Enterprises is being re-directed to purposes other than the basic needs of life, resulting the ongoing poor quality of life. The study also revealed that there is under-representation of women in tourism employment and SMEs. The study recommends that efforts be made to ensure proper co-ordination between leaders and residents and to develop policies that will see women being well represented in tourism employment and SMEs.
Thesis (M.M. (Public and Development Management))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Public and Development Management, 2015.